Aneurysmal bone cyst of maxillary alveolus: A rare case report - Subhas Chandra Debnath; Apurba Kumar Adhyapok; Kriti Hazarika; Kapil Malik; Ashutosh Vatsyayan (Wolters Kluwer Medknow Publications, 2016)
Aneurysmal bone cyst (ABC) is a nonneoplastic rare pathologic entity of the jaws. Its locally aggressive nature and high recurrence rate after curettage make surgical resection a better treatment option. Here, we present a case of ABC of maxillary alveolus and its management by alveolectomy followed by white head varnish pack application in the surgical defect.